PENGARUH SISTEM INFORMASI MANAJEMEN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. DIRGANTARA INDONESIA (PERSERO) - Sjamsuridjal; Fitri Lia Ningsih (JURNAL BISNIS dan TEKNOLOGI, 2019)
PT. Dirgantara Indonesia (Persero) cooperates with Airbus Military to develop CN235 aircraft into CN295. So with the development of the aircraft, Airbus Military requires PT. Dirgantara Indonesia (Persero) to fix the entire production flow in accordance with the specifications of Airbus Military both from human resources, machinery, work environment, systems, and others. One such improvement is the enactment of SAP program management information systems. Research with the title "Effect of Management Information Systems and Competence on Employee Performance of PT. Dirgantara Indonesia (Persero) ", conducted with the aim to determine the effect of management information systems on the performance of employees of PT. Dirgantara Indonesia (Persero) Bandung, the influence of competence on the performance of employees of PT. Dirgantara Indonesia (Persero) Bandung, and the influence of management information systems and competencies on the performance of employees of PT. Dirgantara Indonesia (Persero) Bandung. The population in this study were all permanent employees at PT. Dirgantara Indonesia (Persero). The sample size is 97 permanent employees, sampling using simple random sampling technique. This type of research is a quantitative method by collecting data through questionnaires then analyzed with the help of SPSS Version 20. The data analysis technique uses descriptive analysis and associative analysis (multiple linear regression analysis). The data sources used in this study are primary data obtained from respondents who have been determined by researchers and attendance data of permanent employees as many as 97 people obtained from the Human Resources Department of PT. Dirgantara Indonesia (Persero) as secondary data. Based on the results of the study, it shows that management information systems have a significant influence on the performance of employees of PT. Dirgantara Indonesia (Persero), with a regression coefficient of 0.789 (p-value = 0,000). Competence has a significant influence on the performance of employees of PT.Dirgantara Indonesia (Persero), with a regression coefficient of 0.584 (p-value = 0.007). Management information systems and competencies together have a significant influence on the performance of employees of PT. Dirgantara Indonesia (Persero) of 64.4%.